GERAKAN ISLAM RADIKAL DAN TERORISME DI INDONESIA: KAJIAN TERHADAP UPAYA INTEGRASI BANGSA - Istadiyantha, M. Farhan M, Eva Farhah (Arabic Literature Department, 2013)
Research on Radical Islamic Movement and Terrorism in Indonesia: Study ofIntegration Efforts against Nations will review the symptoms and done by a group ofreligious communities in prioritizing some of the principal teachings of his religion andstudied violence and intimidation from the perspective of religious teachings. How isideology behind the acts of violence and terrorism, and how the views of religious leadersagainst the ideology. On the other hand, it is also assessed the strengths and weaknessesof the government in overcoming the action. It will be found the rules that can be used asa guide for policy makers to undertake preventive measures. This research is useful in politic, sociology and religious field. This research wouldbe useful to inform the public about the ideology and worldview of radical Islamicmovements and terrorism, and its relation to nation integration. Understanding of thenation's character is very important to help the realization of national security system. Acountry having a good separation in nation‟s character will have positive steps toanticipate the problems of national security.